A study of soil deposition as a field laboratory for teaching high school science classes - Castaneda, Azucena A. (1975)
The analysis of soil deposition in San Miguel, Tarlac as a field laboratory for teaching high school science classes was the purpose of this study. This was done by: comparing the soil profile of the area with deposition with the soil profile of the area without deposition; and determining the soil texture, pH, amount of organic matter, phosphorus, and potassium content of the deposited soil in the area being studied and the way in which teachers and students can utilize the findings of this study in their science classes.
Thesis (M.A.T.)--University of the Philippines, Quezon City
Keywords: Science -- Study and teaching (Secondary) -- Philippines; Sedimentation and deposition